Use of a behavioural profile assessment tool for dogs (canis lupus familiaris) in amimal shelters in Occitanie region - Brizon, Charlotte (CCSD, 2021)
In order to improve the quality life of dogs in temporary accommodation places, such as shelters, and to maximize successful adoptions, it is essential to be able to analyze their behaviour as well as possible. To do this, dog behaviour assessment tools exist, although still rare in France. The aim of this study was to test the 4A grid developed by ZOOPSY on 68 dogs from 4 different shelters in Occitanie. Their behaviour, as well as their possible disorders, were evaluated on four main axes: aggressiveness, anxiety, emotional attachment and inhibitory control. The assessments were carried out in the shelters and two additional follow-up assessments are carried out 3 weeks and 3 months after their adoption. The use of this grid in this very specific context made it possible to identify the strengths and weaknesses of the grid and possible improvements, as well as to put forward hypotheses about the behaviours observed in these dogs and their evolution after adoption. Dans une démarche d’amélioration de la qualité de vie des chiens en structure d’hébergement temporaire, telles que les refuges, et pour favoriser le succès des adoptions, il est essentiel de pouvoir décrypter au mieux leur comportement. Pour cela, des outils d’évaluation du comportement canin existent, bien que rares en France. L’étude réalisée ici avait pour objectif de tester la grille 4A développée par ZOOPSY sur 68 chiens issus de 4 refuges d’Occitanie. Leur comportement, ainsi que leurs éventuels troubles, ont été évalués sur quatre axes principaux : l’agressivité, l’anxiété, l’attachement et les autocontrôles. Les évaluations ont été menées au sein des refuges, puis un suivi avec deux évaluations supplémentaires a été réalisé 3 semaines et 3 mois après leur adoption. La mise en pratique de cette grille dans ce contexte très spécifique a permis d’identifier les forces et faiblesses de celle-ci, de proposer des pistes d’amélioration et d’émettre des hypothèses concernant les comportements observés chez ces chiens et leur évolution après ...